การใช้แนวคิดชุมชนการเรียนรู้ทางวิชาชีพเพื่อส่งเสริมความสามารถในการพัฒนา การจัดการเรียนการสอนของนักศึกษาครู - ทับสาย บุญสม (Journal of Education Studies, Chulalongkorn University, 2019)
The purposes of this actionresearch were to: 1) study the capacityof student teachers to improveinstructional implementation, and 2) propose the process for enhancing the capacity of student teachers to improve instructional implementationbased on the professional learning community approach. Six student teachers voluntarily participated in the study. The research instruments were an instructional implementation reflective form, an instructional practice evaluation form, and a phonics instruction observation form. Data was analyzed by content analysis, mean,standard deviation, and interrater reliability. The findings of this research were as follows: 1) The pilot process enabled all participating student teachers to reflect and design instructionto adjust instructional implementation.In addition, the general instructional practice and synthetic phonics instruction abilities of student teachers were at very good level. 2) The process piloted in this study consisted of 7 steps: (1) determine student and student teacher learning needs,(2) identify student and aligned student teacher learning goals, (3) develop student teachers’ knowledge and skills, (4) design instruction and reflect on lesson plans, (5)implement instruction, (6) observe and reflecton instructional implementation, and (7) evaluate and reflect on student and student teacher learning results.